Motor DC Dengan Penyearah Tak Terkontrol Tiga Fasa Gelombang Penuh Berbasis PSIM - Nugraha, Anggara Trisna (Universitas Muhammadiyah Ponorogo, 2023)
In this era, people are very dependent on electric motors. The use of electric motors covers various fields, ranging from household appliances, industrial equipment, robots, airplanes, computers, and other electronic devices that require electric motors for propulsion. With the advancement of today's engine technology, the engine is expected to be reliable and provide maximum efficiency characteristics. To achieve this, you can make the following changes to some parts of the machine to make it work properly and with maximum efficiency. Below is a flow chart that begins with observing and looking for literary studies in journals, books, and dissertations. After finding the concept from observations, making a circuit with PSIM, entering these parameters, then looking for the parameters of the DC motor components, then the circuit design is carried out. After the circuit is complete, PSIM will run the simulation. If you have already measured the existing parameters. After the survey is conducted, a survey report is generated. This study helps to design a fully uncontrolled rectifier system for DC motors to minimize design errors made in the field. That is, using PSIM software. In this experiment, there are several obstacles that even greatly affect the final results of the experiment which are not optimal and not convincing.